The Character of Ecological People in the Quran: A Thematic Interpretation Study - Nihayah, Hamidatun; Jamil, M. Mukhsin (Al Ulya: Jurnal Pendidikan Islam, 2024)
The harmonious relationship between humans and their environment can be likened to a mutually beneficial relationship. This perspective views humans as an inseparable element of their environment, with an emphasis on the human obligation to care for and ensure the survival of nature. In return, nature will provide benefits to fulfil human needs. This research aims to actualise ecological verses in human life and produce the proposition of theological insanity from the perspective of the Quran. The following research method is a qualitative approach focusing on library research. As a guide and reference, it uses library data sources. When viewed from the method of analysis, it can be classified as descriptive research that describes information based on events and facts and relates it to explanations from related sources according to the topic of this research. In analysing Quranic interpretation, the following includes thematic or maudhûi interpretation research, with steps, namely collecting Quranic verses related to humans, the environment and nature. Furthermore, it provides interpretation and understanding of the verses in question through the application of various contemporary interpretation sources combined with other sources. This research produces a proposition of ecological human character in the Quran, which includes Khalifah, Hikmah, and Mizan. Thus, three things are interrelated to create the character of the rahmatan li al 'alamin people.